(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Accurate identification of subject–predicate relations is a foundational requirement for successful translation into English, particularly from languages with flexible word order and rich morphology such as Uzbek. While subject–predicate structure has been extensively discussed in descriptive and theoretical grammar, its direct methodological relevance to translation practice remains underexplored. This article reworks and extends a prior course paper by reframing the analysis of English subject–predicate groups through a translation-oriented lens. Drawing on structural, functional, and contrastive linguistic approaches, the study proposes a methodology for identifying subject–predicate relations in source texts and preserving or strategically restructuring them in English translation. The paper combines qualitative sentence analysis with contrastive examples from English and Uzbek to demonstrate how syntactic misidentification leads to translation shifts, ambiguity, or loss of emphasis.